2013
DOI: 10.1002/ar.22756
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth, Glomerular Number, and Tubular Proteins in the Developing Rhesus Monkey Kidney

Abstract: An essential step in the translation of cell-based therapies for kidney repair involves preclinical studies in relevant animal models. Regenerative therapies in children with congenital kidney disease may provide benefit, but limited quantitative data on normal development is available to aid in identifying efficient protocols for repair. Nonhuman primates share many developmental similarities with humans and provide an important translational model for understanding nephrogenesis and morphological changes acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Cells lining the lumen of larger tubules typically displayed an epithelial morphology and expressed cytokeratin, but not vimentin ( Fig 5E–5H ). Early renal lineage markers WT1 and PAX2 were expressed in distinct regions under Protocol A on both types of scaffold materials ( Fig 5I and 5J ) in a pattern similar to mid- to late-first trimester kidney development where the PAX2-positive ureteric bud is surrounded by WT1-positive metanephric mesenchyme [ 28 ]. Under Protocol B, PAX2-positive cells surrounded WT1-positive tubules for cultures on renal ECM with a more diffuse staining pattern observed in PSS ( Fig 5K and 5L ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells lining the lumen of larger tubules typically displayed an epithelial morphology and expressed cytokeratin, but not vimentin ( Fig 5E–5H ). Early renal lineage markers WT1 and PAX2 were expressed in distinct regions under Protocol A on both types of scaffold materials ( Fig 5I and 5J ) in a pattern similar to mid- to late-first trimester kidney development where the PAX2-positive ureteric bud is surrounded by WT1-positive metanephric mesenchyme [ 28 ]. Under Protocol B, PAX2-positive cells surrounded WT1-positive tubules for cultures on renal ECM with a more diffuse staining pattern observed in PSS ( Fig 5K and 5L ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of immunohistochemical markers was carried out according to established protocols for glomerular, tubular, and renal developmental markers [ 27 , 28 ]. The primary antibodies utilized in the study are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, stereological techniques were used for the quantification of volume, volume fraction, glomerular number, and PCT and DCT length of the cat kidney. Stereological methods are known as reliable, precise, and efficient methods for quantifying kidney structures, which contain important information about the renal function and organization (Nyengaard, ; Batchelder et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most stereological investigations on the kidney have been carried out on laboratory animals such as mouse (Arsenault et al, ; Walton et al, ; Nuñez et al, ) and rat (Şimşek et al, ; Khoshvakhti et al, ; Melchioretto et al, ; Seravalli et al, ), and also on other mammals such as nonhuman primates (Gubhaju and Black, ; Batchelder et al, ). However, apart from investigations on the kidney in pig (Cibulskyte et al, ; Karstoft et al, ; Lødrup et al, ,b), sheep (Bains et al, ; Wintour et al, ) and horse (Bolat et al, ), the morphometric features of kidney of other domestic animals have not been thoroughly investigated using stereology.…”
mentioning
confidence: 99%
“…In the normal kidney, proximal tubules, rare Bowman's capsule epithelium, descending thin limbs of long looped nephrons, descending vasa recta, glomerular and vascular endothelium, and red blood cells had AQP1þ cytoplasmic and membrane immunostaining. [54][55][56] In the affected kidney, there were only a few small poorly differentiated cortical tubules that stained AQP1þ, although nests of morphologically mature proximal tubules stained positive. Also, occasional Bowman's capsule epithelium had increased AQP1þ immunostaining (not shown).…”
Section: Aquaporinmentioning
confidence: 99%